Allegories for Psychotherapy, Teaching, and Supervision Windows, Landscapes, and Questions for the Traveler - Kunkel, Mark A. (Springer International Publishing, 2018)
This book explores the practice of psychotherapy, teaching, and supervision via allegory, metaphor, and myth. Based upon the author's own extensive teaching and practice, Mark Kunkel takes the reader through a series of vignettes that are windows not only into reality, but also into the soul. The author's approach reflects his vocational commitment to an integration of conceptualization, affective involvement, and application. These allegories, parables, and myths serve to clarify and open important issues in teaching, psychotherapeutic, and clinical supervisory settings, and are intended to be allies in individual study and group discussion alike. .